Association of HTN with Silent Brain Infarcts on MRI in Asymptomatic Patients - Babar, Masood Uz Zaman; Ahmed, Faraz; Munir, Akram; Akhtar, Asfahan; Abbas, Saira; Ali, Manzoor (Journal of Neonatal Surgery, 2025)
Background: Hypertension (HTN) is a well-established risk factor for cerebrovascular disease, including the occurrence of silent brain infarcts (SBIs), which are often subclinical and asymptomatic. Objective: The objective of this study was to assess the association between HTN and the prevalence of SBIs in asymptomatic patients. Methods: This cross-sectional observational study was conducted at Isra University Hyderabad during November 2023 to September 2024. A total of 85 patients were included in this study. Demographic variables such as age, gender, and relevant clinical data, including the duration of hypertension, were collected. Blood pressure measurements were taken, and information on comorbidities such as smoking, diabetes, and dyslipidemia was obtained. Results: Among the 85 participants, 31 (37%) had silent brain infarcts. The prevalence of SBIs was significantly higher in patients with Stage 2 hypertension (47%) compared to Stage 1 hypertension (30%). The prevalence of SBIs also increased with the duration of hypertension, with 52% of patients with hypertension lasting more than 10 years showing SBIs. There was no significant difference in the presence of SBIs between patients on antihypertensive medication and those not on medication (p = 0.50). Comorbidities such as smoking and diabetes were also associated with a higher prevalence of SBIs. Conclusions: It is concluded that hypertension, particularly long-standing and severe cases, is significantly associated with the presence of silent brain infarcts in asymptomatic patients.